Unusually strong nitric oxide descent in the Arctic middle atmosphere in early 2013 as observed by Odin/SMR - K. Pérot; J. Urban; D. P. Murtagh (Atmospheric Chemistry and Physics, 2014)
The middle atmosphere was affected by an exceptionally strong midwinter stratospheric sudden warming (SSW) during the Arctic winter 2012/2013. These unusual meteorological conditions led to a breakdown of the polar vortex, followed by the reformation of a strong upper stratospheric vortex associated with particularly efficient descent of air. Measurements by the submillimetre radiometer (SMR), on board the Odin satellite, show that very large amounts of nitric oxide (NO), produced by energetic particle precipitation (EPP) in the mesosphere/lower thermosphere (MLT), could thus enter the polar stratosphere in early 2013. The mechanism referring to the downward transport of EPP-generated NO x during winter is generally called the EPP indirect effect. SMR observed up to 20 times more NO in the upper stratosphere than the average NO measured at the same latitude, pressure and time during three previous winters where no mixing between mesospheric and stratospheric air was noticeable. This event turned out to be the strongest in the aeronomy-only period of SMR (2007–present). Our study is based on a comparison with the Arctic winter 2008/2009, when a similar situation was observed. This outstanding situation is the result of the combination of a relatively high geomagnetic activity and an unusually high dynamical activity, which makes this case a prime example to study the EPP impacts on the atmospheric composition.